Recent advances in wavelet analysis: Part 2 - Amazone, Parana, Orinoco and Congo interannual and multidecadal variability - Labat, David; Ronchail, Josyane; Guyot, Jean-Loup (Journal of Hydrology, 2005)
This paper is devoted to illustrating new wavelet analysis methods in the field of hydrology. New wavelet indicators are applied to long-term hydrological and climatologic proxies. They are first applied to four Atlantic large river monthly discharges (Amazon, Parana, Orinoco and Congo) and then applied to two well-known long-term climatologic indexes: the Southern Oscillation and the North Atlantic Oscillation. This approach makes it possible to suggest physical explanations for time scale dependant relationships. Six-month variability is present in all the rivers except in the Parana. In the Congo River this signal is near stationary with strong entropy. The strength of this scale coincides with higher discharge variability before 1920 and over the Orinoco basin with higher discharge values between 1940 and 1955. An annual cycle is present in all the rivers but is much stronger, along with the entropy, in the rivers with a large tropical basin, as in the Amazon and the Orinoco. This annual signal is not permanent in the Congo and much more intermittent in the Parana where the annual recharge appears as very irregular. A quasi biennial variability is apparent in all the equator ward rivers and a nearly permanent 2-year coherence is found between SOI and the Amazon discharge. A 3 6-year oscillation typical of ENSO variability is observed in all the rivers. It is intermittent, observed before 1930 in all the rivers and after 1980 mostly in the Amazon River. These peaks of activity correspond to periods of major SOI variability. An 8-year variability is particularly strong in the Parana River before 1940 and around 1970 and to a lesser extent in the Orinoco River during the low NAO index period, between 1940 and 1970. The Congo River exhibits that time scale around 1970. A 13-year variability common to SOI, NAO and the South Atlantic Ocean circulation is observed in the Parana and Congo discharges. In all the rivers the greatest entropy is observed at bi and multi decadal time scales with the greatest coherence ...